HUBUNGAN STRESS TERHADAP SIKLUS MENSTRUASI MAHASISWI - Fransiska, Nia; Srimiyati, Srimiyati; Romlah, Romlah (Journal of Holistic Nursing Science, 2017)
Background: Stress is a reaction both physical and psychic to any demands that cause tension that can disrupt the stability of life that will affect the hormonal system of the body one of the effects is the change of menstrual cycle. Objective: The objective of this study was to determine the relationship of stress level to menstrual cycle female. Method: analytic survey, design Cross Sectional approach. The sample in this research is student of health faculty of Catholic university of Palembang musi charitas as many as 91 respondents selected by used purposive sampling technique and calculated by slovin formula. Result: univariate analysis result showed 13 (14.3%) of 91 respondents had mild stress, 19 (20.9%) had moderate stress 59 (64.8%) and there were 47 people (51%) of 91 respondents had abnormal menstrual cycle and 44 people (48.4%) had a normal menstrual cycle. The result of bivariate analysis with statistical test of kendall tau showed there was no significant relationship between stress level to menstrual cycle (p >0.05). respondents are advised to make efforts to prepare themselves early in the face of the learning process and the final project so that the stres that occurs can be minimized or prevented.